1993
DOI: 10.1021/ja00071a032
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly and photophysical properties of lanthanide dinuclear triple-helical complexes

Abstract: The dinucleating ligand bis[ 1- methyl-2-(6'- [ 1”-(3,5 imethoxybenzyl)benzimidazol-2~'-ylp]y rid-2'-y1)benzimidazol- 5-yllmethane (L) reacts with lanthanide perchlorates to give dinuclear 2:3 complexes [Lnz(L)#+ (Ln = La, Eu, Gd, Tb, and Lu). Detailed ES-MS, lH-NMR, luminescence, and spectrophotometric measurements in acetonitrile show that the cations [Ln2(L)#+ are produced by strict self-assembly and adopt a triple-helical structure in solution (pseudo-D3s ymmetry). The crystal structure of [EU~(L)~] C~O~)~… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
269
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 309 publications
(294 citation statements)
references
References 0 publications
24
269
1
Order By: Relevance
“…3 fully confirms the structural data obtained in solution, the three ligand strands being helically wrapped around the two metal ions and the three amide functions being coordinated to the heaviest metal ion, Eu III . Bond lengths and angles of the coordination polyhedron are standard for the two ions and compare well, after correction for ionic radius differences, with those found in the previously reported homodimetallic structures of [Eu 2 (L A ) 3 ] 6+ , 8 [Tb 2 (L B ) 3 ] 6+ , 9 and [Ln 2 (L C -2H) 3 ] (Ln = Eu, Tb, Yb). 10 In conclusion, we have presented here the first design of an unsymmetrical ditopic ligand coded for the supramolecular recognition of two different lanthanide ions.…”
Section: T H I S J O U R N a L I S © T H E R O Y A L S O C I E T Y O supporting
confidence: 77%
“…3 fully confirms the structural data obtained in solution, the three ligand strands being helically wrapped around the two metal ions and the three amide functions being coordinated to the heaviest metal ion, Eu III . Bond lengths and angles of the coordination polyhedron are standard for the two ions and compare well, after correction for ionic radius differences, with those found in the previously reported homodimetallic structures of [Eu 2 (L A ) 3 ] 6+ , 8 [Tb 2 (L B ) 3 ] 6+ , 9 and [Ln 2 (L C -2H) 3 ] (Ln = Eu, Tb, Yb). 10 In conclusion, we have presented here the first design of an unsymmetrical ditopic ligand coded for the supramolecular recognition of two different lanthanide ions.…”
Section: T H I S J O U R N a L I S © T H E R O Y A L S O C I E T Y O supporting
confidence: 77%
“…[14] Above 200 K, the lifetimes of both sites in [Eu 3 (L7) 3 ] 9 sharply decrease to reach 1.7(1) ms at 295 K, because of thermally activated vibrational-quenching processes. Interestingly, the lifetime of the central EuN 9 sites is less affected at 295 K than that reported for the bimetallic model complex [Eu 2 (L1) 3 ] 6 (t 0.29(1) ms at 295 K); [13] …”
Section: Introductionmentioning
confidence: 68%
“…Factor analysis [23] points to the existence of four absorbing species (L7, [Ln 2 (L7) 3 ] 6 , [Ln 3 (L7) 3 ] 9 , and [Ln 3 (L7) 2 ] 9 ) in agreement with the ESI-MS results, and the spectrophotometric data can be fitted with nonlinear least-squares techniques [24] to the equilibria given in Equations (1) ± (3), which characterize the assembly process (the formation constants log(b Ln ij are collected in Table 1). 17.5 ± 20.0); [13] ring between the closely packed benzimidazole rings (vide infra, Figure 6) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of this difficulty, we have demonstrated that a careful ligand design based on the induced fit principle [20] leads to the strict selfassembly of lanthanide-containing triple-stranded helicates in organic media. [21,22] Ditopic pentadentate, hexadentate or nonadentate ligands derived from 2-pyridin-2-yl-1H-benzimidazole are indeed versatile building blocks and can be used to prepare bimetallic 3dϪ4f and 4fϪ4f assemblies, [23] as well as trimetallic 4fϪ4fϪ4f edifices. [24] Recently, we have also shown that grafting different substituents at the end of the hexadentate ligands results in ditopic hosts able to specifically recognize a pair of lanthanide ions in solution.…”
Section: Introductionmentioning
confidence: 99%